COMPLETELY Î³ - GENERALIZED CONTINUOUS MAPPINGS IN INTUITIONISTIC FUZZY TOPOLOGICAL SPACES - S, PREMA; D, JAYANTHI (International Journal of Mathematical Archive, 2018)
In this paper we introduce intuitionistic fuzzy completely Î³ generalized continuous mappings. We investigate some of their properties. Also we provide some characterization of intuitionistic fuzzy completely Î³ generalized continuous mappings.